The Chase - Connell, Arthur (Tufts Archival Research Center, 2006)
Arthur Connell, National Commander of the American Legion, describes his belief that every human being has a purpose from God and the potential to do good, and that every circumstance happens for a reason, even the death of his only daughter. Audio also contains advertisement for "This I Believe" book.